Characterization of FA1654: A putative DPS protein in Filifactor alocis. (19th December 2022) - Mangar, Malissa; Mishra, Arunima; Yang, Zhengrong; Deivanayagam, Champion; Fletcher, Hansel M.
Abstract: The survival/adaptation of Filifactor alocis, a fastidious Gram‐positive asaccharolytic anaerobe, to the inflammatory environment of the periodontal pocket requires an ability to overcome oxidative stress. Moreover, its pathogenic characteristics are highlighted by its capacity to survive in the oxidative‐stress microenvironment of the periodontal pocket and a likely ability to modulate the microbial community dynamics. There is still a significant gap in our understanding of its mechanism of oxidative stress resistance and its impact on the virulence and pathogenicity of the microbial biofilm. Coinfection of epithelial cells with F. alocis and Porphyromonas gingivalis resulted in the upregulation of several genes, including HMPREF0389_01654 (FA1654) . Bioinformatics analysis indicates that FA1654 has a "di‐iron binding domain" and could function as a DNA starvation and stationary phase protection (DPS) protein. We have further characterized the FA1654 protein to determine its role in oxidative stress resistance in F. alocis . In the presence of hydrogen peroxide‐induced oxidative stress, there was an ∼1.3 fold upregulation of the FA1654 gene in F. alocis . Incubation of the purified FA1654 protein with DNA in the presence of hydrogen peroxide and iron resulted in the protection of the DNA from Fenton‐mediated degradation. Circular dichroism and differential scanning fluorimetry studies have documented the intrinsic ability of rFA1654 protein to bind iron; however, the rFA1654 protein is missing the intrinsic ability to reduce hydrogen peroxide. Collectively, the data may suggest that FA1654 in F. alocis is involved in oxidative stress resistance via an ability to protect against Fenton‐mediated oxidative stress‐induced damage.